Gender role orientation of husbands and work-family conflict of wives in dual-earner families - Ahmad, Aminah (Universiti Putra Malaysia Press, 1999)
This study examined the intensity of work-family conflict experienced by married working women, the gender role orientation of their husbands, and the relationship between husbands' gender role orientation and wives' work-family conflict. Responses from 125 pairs of nurses and their husbands in dual-earner families on measures of work-family conflict and gender role orientations were obtained through self-administered questionnaires and analysed. Results indicated that nurses experienced varying intensities of conflict in trying to meet the demands of work and family roles. Almost a third of the nurses experienced high intensity of conflict while slightly more than a third experienced low intensity of conflict. Husbands' gender role orientation ranged from traditional to egalitarian with about a quarter of them holding traditional gender role orientation and slightly more than a quarter holding egalitarian orientation. Among the three dimensions of orientation studied, namely, attitude towards gender-based employment, attitude towards gender division of labour and attitude towards gender-based power structure, husbands' orientation was traditional toward power structure or toward women occupying leadership positions. Their orientation toward gender division of labour was neither egalitarian nor traditional while their orientation toward gender-based employment was more egalitarian. Significant negative relationship was found between husbands' gender role orientation and wives' work-family conflict.